2021
DOI: 10.3390/su13147702
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Wind Energy Potential as a Driver of Sustainable Development in the Southern Coasts of Iran: The Importance of Wind Speed Statistical Distribution Model

Abstract: Wind energy as a clean and inexhaustible source of renewable energy can be a key element of sustainable development that decreases dependence of countries on fossil fuels. Therefore, implementing accurate and comprehensive feasibility studies in countries with a high level of consumption of traditional energy resources is vital; an approach encouraged and supported by green funds and climate change action. It is also crucial to helping spur economic and sustainable growth of these countries. In this regard, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Ten locations were selected to evaluate the cost implication of wind power generation across these sites. Twenty-four years data from 1987 to Filom et al (2021). range between 2.9 and 5.8 m/s -showing suitability for large scale wind power generation.…”
Section: Nigeria Onshore Wind Energy Potentialmentioning
confidence: 99%
“…Ten locations were selected to evaluate the cost implication of wind power generation across these sites. Twenty-four years data from 1987 to Filom et al (2021). range between 2.9 and 5.8 m/s -showing suitability for large scale wind power generation.…”
Section: Nigeria Onshore Wind Energy Potentialmentioning
confidence: 99%
“…(3) Based on the findings in [45] , which are the motivation to find out the relationship between the wind power generated based on the area requirement, it can be concluded that the Karimunjawa Island area is 71.2 km 2 the wind energy density on Karimunjawa Island is 400 w/m 2 . This wind energy density is classified as "Good" [47] or ranked in the 4th [48,49], but the classification at the average wind speed is 7 m/s. On the other hand, the average wind speed on the island of Karimunjawa is 3.67-4.76 m/s, so it can be concluded that it is not feasible to build wind power plants.…”
Section: Levelized Cost Of Electricity (Lcoe) and Electric Production...mentioning
confidence: 99%
“…Various forms of renewable energy, including wind power, biopower, solar power, geothermal power, and ocean power, derive their energy from the sun. With the exception of geothermal and ocean energy, these sources are considered infinite and environmental-friendly (Filom et al, 2021). Wind energy, in particular, stands out as a clean and reliable source, converting about 1-2 percent of the sun's energy into an endless power supply, surpassing the energy conversion of all Earth's plants combined by 50-100 times (Amini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%